Complication and remission rates after endoscopic argon plasma coagulation in the treatment of haemorrhagic radiation proctitis - Siow, Sze Li; Mahendran, Hans Alexander Lexander; Seo, C. J. (Springer Verlag, 2017)
Purpose: The management of haemorrhagic radiation proctitis is challenging because of the necessity for repeated intervention. The efficacy of argon plasma coagulation has been described before but the optimum treatment strategy remains debatable. This is a review of our experience over a decade treating patients with haemorrhagic radiation proctitis and their follow-up. Methods: This is a retrospective review of consecutive patients who underwent argon plasma coagulation for haemorrhagic radiation proctitis between January 2003 and December 2013. The patients were followed up using a prospectively maintained database. Results: Ninety-one patients were included with a mean follow-up of 13.1 months. Majoity (n = 85, 93.4 %) of the patients were female. Mean age at the time of treatment was 58.2 (range 23–87) years old. Majority of the patients (n = 73, 80.2 %) received radiotherapy for gynaecological malignancies followed by colorectal (n = 13, 14.3 %) and urological (n = 5, 5.5 %) malignancies. Mean interval between radiation and proctitis was 13.8 (range 3–40) months. Seventy-nine percent of patients were successfully treated after 1–2 sessions. Seventeen (18.7 %) patients experienced self-limiting early complications, and three (3.3 %) had late complications of rectal stenosis which was managed conservatively. Severity of bleeding during the initial presentation is an independent factor that predicts the number of sessions required for successful haemostasis (p = 0.002). Conclusions: Argon plasma coagulation is a reasonable treatment option in patients with haemorrhagic radiation proctitis with good safety profile. Our study suggests that the number of APC sessions required to arrest bleeding correlates with the severity of bleeding on initial presentation.